Presence of Candida zemplinina in Sicilian Musts and Selection of a Strain for Wine Mixed Fermentations - Di Maio, S.; Genna, G.; Gandolfo, V.; Amore, G.; Ciaccio, M.; Oliva, D. (South African Journal of Enology and Viticulture, 2016)
The purpose of this work was to investigate the presence of C. zemplinina yeasts in Sicilian musts and grapes and to identify strains of oenological interest. We report on the taxonomical reclassification of Candida yeast isolates from Sicilian musts and on the selection of one strain of oenological interest (Cz3), based on mixed micro-fermentation experiments in sterile Nero d’Avola musts. Our results show that Candida zemplinina is abundant in Sicilian grapes and musts, and that the Cz3 strain is suitable for Candida zemplinina/Saccharomyces cerevisiae mixed fermentations. The higher glycerol content and the lower ethanol level stood out as the most promising features of the wines obtained upon sequential inoculation of the Cz3 and (S. cerevisiae) NDA21 yeast starters. We therefore have isolated a Sicilian Cz strain endowed with very promising features for the future development of mixed fermentation protocols.